Deriving the normalised ion-neutral collision frequency from EISCAT observations - J. A. Davies; M. Lester; T. R. Robinson (Annales Geophysicae, 1997)
Common programme observations by the EISCAT UHF radar revealed an extended interval, post geomagnetic local noon on 03 April 1992, during which the F-region ion velocity orthogonal to the geomagnetic field was significantly enhanced, to values exceeding 2 km s –1 corresponding to a perpendicular electric field of some 100 mV m –1 . Observations from this interval are used to illustrate a method by which estimates of the E-region ion-neutral collision frequency may be derived in the presence of enhanced electric field. From both the rotation of the ion velocity vector and the reduction in the ion velocity magnitude relative to that in the F-region, independent estimates of the normalised ion-neutral collision frequency are made at the UHF E-region tristatic altitudes; the derived values are, in general, lower than model predictions. Although initial calculations assume a stationary neutral atmosphere, first-order estimates of the E-region neutral wind are subsequently employed to calculate revised estimates of the normalised ion-neutral collision frequency; these neutral winds are derived by attributing the difference between predicted and observed enhancements in field-parallel ion temperature to thermospheric motion. The inclusion of neutral winds, which are themselves not inconsiderable, appears to have only a limited effect on the normalised collision frequencies derived.